The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1243/0954411011533481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of simulator kinematics on the wear of metal-on-metal hip prostheses

Abstract: There is now considerable interest in metal-on-metal bearings for hip prostheses. Extremely low wear rates (0.1 mm3/10(6) cycles) have been reported in some simulator studies, while in vivo studies, although still very low, have shown wear rates of the order of 1 mm3/10(6) cycles. The aim of this study was to compare wear rates of metal-on-metal bearings in two hip simulators with different kinematic inputs. In the simulator with three independent input motions which produced an open elliptical wear path with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 5 publications
3
26
0
Order By: Relevance
“…15,21 Analysis of the wear paths produced by different simulators has shown a wide variation, ranging from simple linear paths with infinite aspect ratios to open circular paths with low aspect ratios. 22 The potential importance of variations in individual THA patient's wear paths on wear rates has recently been recognized, with altered gait cycle inputs used to predict wear rate in a finite element model.…”
Section: Discussionmentioning
confidence: 99%
“…15,21 Analysis of the wear paths produced by different simulators has shown a wide variation, ranging from simple linear paths with infinite aspect ratios to open circular paths with low aspect ratios. 22 The potential importance of variations in individual THA patient's wear paths on wear rates has recently been recognized, with altered gait cycle inputs used to predict wear rate in a finite element model.…”
Section: Discussionmentioning
confidence: 99%
“…The weight-loss curve for the GUR 1020 polyethylene is nearly identical to that published by McKellop in 1997 for the same material, 27 confirming that the data being generated is consistent with that being produced in other laboratories. Other published studies of hipsimulator wear of metal-on-metal bearings have reported wear rates two times, 28 four times, 29 and up to nine or ten times 30,31 with the use of metal-on-metal bearing combinations with similar radial clearances but using serum that had been diluted to 25% as a lubricant. One of these studies 30 also involved the use of nearly undiluted (90%) serum with wear rates similar to those of the current research.…”
Section: Discussionmentioning
confidence: 99%
“…13,20,21 The particle sizes were typically Ͻ100 nm. Such a wear debris fraction has been generated using the disc-on-pin apparatus.…”
Section: Particlesmentioning
confidence: 99%